2016
DOI: 10.1002/ana.24553
|View full text |Cite
|
Sign up to set email alerts
|

DNAJC6Mutations Associated With Early‐Onset Parkinson's Disease

Abstract: Our findings delineate a novel form of hereditary early-onset PD. Screening of DNAJC6 is warranted in all patients with early-onset PD compatible with autosomal recessive inheritance. Our data provide further evidence for the involvement of synaptic vesicles endocytosis and trafficking in PD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 48 publications
1
76
0
Order By: Relevance
“…(Bonifati, 2014). The clinical phenotype of DNAJC6-mediated PD includes a rapid disease course with poor response to L-DOPA, pyramidal signs, seizures, mental retardation, and dystonia (Olgiati et al, 2016). Patients with pathogenic SYNJ1 mutations also present with a rapid disease course; however, progression stabilizes in later stages of the disease.…”
Section: Other Rare Arpd Genesmentioning
confidence: 99%
“…(Bonifati, 2014). The clinical phenotype of DNAJC6-mediated PD includes a rapid disease course with poor response to L-DOPA, pyramidal signs, seizures, mental retardation, and dystonia (Olgiati et al, 2016). Patients with pathogenic SYNJ1 mutations also present with a rapid disease course; however, progression stabilizes in later stages of the disease.…”
Section: Other Rare Arpd Genesmentioning
confidence: 99%
“…Several recent studies have revealed a link between proteins that participate in synaptic vesicle endocytic recycling, clathrin mediated endocytosis in particular, and early onset Parkinsonism (EOP) (Edvardson et al, 2012; Koroglu et al, 2013; Krebs et al, 2013; Olgiati et al, 2014; Olgiati et al, 2016; Quadri et al, 2013; Schreij et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In these patients Parkinson-like symptoms developed in early adulthood (20–30’s) and 4 of them additionally suffered from epilepsy (Drouet and Lesage, 2014). This finding is of striking interest, as loss-of-function mutations in the gene DNAJC6 that encode auxilin, another protein that functions in the uncoating of endocytic CCVs (Fotin et al, 2004; Ungewickell et al, 1995), are also responsible for autosomal recessive juvenile Parkinson’s disease (PD) and sporadic cases of PD, leading to define auxilin as PARK19 (Edvardson et al, 2012; Koroglu et al, 2013; Olgiati et al, 2016). Based on studies of the purified protein, the EOP mutation of SJ1 (SJ1 R->Q ) selectively abolishes the phosphatase activity of the Sac domain without affecting the activity of the 5-phosphatase domain (Krebs et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By sequencing the DNAJC6 gene in patients with early-onset PD, Olgiati et al discovered three patients with double mutations in this gene [76••]. Two of them had familial disease, and analysis of affected and unaffected family members showed complete co-segregation.…”
Section: New Genes For Recessive and X-linked Pd Or Parkinsonismmentioning
confidence: 99%